PENGARUH PENGGUNAAN SOFTWARE ZAHIR POSX TERHADAP MANAJEMEN BISNIS USAHA MIKRO KECIL DAN MENENGAH DI KOTA SAMARINDA - Martinus Robert Hutauruk; Siti Rohmah; Agus Rudolf Rihi; Desna Reti; Nur Lutfy hanif (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2019)
The development of information technology which is the impact to development revolution of industrial 4th makes every activity inseparable from network usage with entrepreneurs in the Micro, Small and Medium Enterprises (UMKM) group, who also must be albe to capture the business opportunity. The purpose of this study is to confirm the role of Zahir POSX software on business management in the UMKM group in Samarinda city. This research was conducted on 275 populations in the UMKM group located in Samarinda City, especially in the area around Mulawarman University and University of Widya Gama Mahakam Samarinda, and by using the Slovin method with a 5% error rate, 163 respondents were taken as sample. Test on validity and reliability have been darried out with good results on the items received agin before further analysis. This study was conducted in order to predict the role of Zahir POSX software on business Management and used the Structural Equation Modeling (SEM) wih multiple groups through Smart PLS Version 3.2.8 software. The results of this study found that on use Zahir POSX software had a positive and significant impact on UMKM group in Samarinda. Entrepreneurs will be easier in controloing their business, even using paper less media. The results also show that through modern accounting software, it will increasingly make business management more effective and efficient